Population Density Effects on Carapace Growth in Clam Shrimp: Implications for Palaeontological Studies - Hethke, Manja (Zool Stud, 2020)
Fossil morphological data are time-averaged and generally reflect an overlap of different sources of carapace variability. To examine whether a proposed relationship between size and population density in fossil spinicaudatans is biologically meaningful, we set up rearing experiments involving two extant species: Eulimnadia texana and Eocyzicus argillaquus. Three and five days after hydration, clam shrimp were transferred into cups of various population densities that ranged between 1 and 15 inds/400 ml. Size and shape were measured 14 and 16 days after hydration, respectively. Every second day, we recorded length and sex of E. texana, which matured faster in lower-density cups. According to our growth model, population density and maximal carapace length follow a logarithmic relationship. At maturity, hermaphrodites yielded similar lengths across all population densities (~4.7 mm at 24°C), independent of age. Hence, clam shrimp can put off reproductive maturity as a response to decreased growth under higher density conditions. Growth rate generally decreases at maturity, but that effect is more pronounced in clam shrimp of high population densities, while low-density adults keep growing. For both species, multivariate analyses reveal that carapace size of low-density individuals is significantly larger than carapace size of higher-density individuals, while size values of intermediate densities cannot be distinguished. Shape distinction is strong in hermaphrodites of E. texana: 39.8% of the density-dependent shape variation is associated with relative umbo height, which is generally higher in individuals of smaller population densities. The H/L ratio, which is often used as a simple shape indicator, does not contribute to the main variation in shape, but it forms one of several ratios significant for 18.3% of the shape variability. In turn, the H/L ratio drives 30% of the shape variation in E. argillaquus. In addition, higher densities triggered shifts in ontogenetic growth trajectories in one third of the individuals, which led to aberrant morphologies. The present rearing experiment shows that some of the morphological variability on fossil bedding planes can be explained by population density. Also, it implies a considerable amount of ecophenotypic variability in Spinicaudata that affects our understanding of fossil taxonomy and palaeoecology.